Respons Tulang Femur Tikus Ovariohisterektomi yang Mengkonsumsi Kasein dan Disuplementasi Calcitriol Selama 30 Minggu (THE RESPONSE OF BONE FEMUR OVARIOHISTERECTOMIZED RATS CONSUMING CASEIN AND CALCITRIOL SUPPLEMENTATION FOR 30 WEEKS) - Hartiningsih, Hartiningsih; Anggraeni, Devita; Widiyono, Irkham; Wuryastuty, Hastari (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
Calcitriol supplementation in ovariohisterectomized rat was known to decreased calcium retention.The objective of the research was to study the response of femur bone to calcitriol supplementation for 30weeks in ovariohisterectomized rats consuming casein. Twenty female Wistar rats at 8 weeks of age wererandomly divided into four groups (unovariohisterectomy without calcitriol supplementation (N),unovariohisterectomy with calcitriol supplementation (ND), ovariohisterectomy without calcitriolsupplementation (O) and ovariohisterectomy with calcitriol supplementation (OD) of five each. Thirtyweeks after surgery, femur was taken for histopathological and immunohistochemistry examination.Immunohistochemistry of distal femur metaphysis in group O and OD were revealed decreasing tartrateresistant alkaline phosphatase 5b (TRAP5b) in trabecular bone, which was located in bone marrow space,and also in trabecular speculum surface. Histopathological analysis of distal femur metaphysis in groupN and ND were showed normal structure, meanwhile, distal femur metaphysis in group O and OD wereshown some abonormalities, such as increased of bone marrow space, domination of adipocytes in the bonemarrow, and decreased of trabecular bone speculum in metaphysis. Based on the results, it was concludedthat femur bone of ovariohisterectomized rats fed casein with and without calcitriol 8ng/daysupplementation for 30 weeks were showed unbalanced between resorption and formation of bone whichwas domination by bone resorption.
Keywords: calcitriol, femur, ovariohisterectomy